Effect of educational intervention addressing inaccurate self-assessment of driving performance in older Japanese adults. (December 2021) - Kosuge, Ritsu; Okamura, Kazuko; Nakano, Yukako; Fujita, Goro
Highlights: We developed a feedback intervention for accurate self-assessment in older drivers. The intervention improved the accuracy of self-assessment. General driving performance improved after the intervention. Vehicle speed at intersection with a stop sign was likely to reduce. Abstract: To maintain road safety for older drivers as well as other road users, it is important to provide interventions that improve self-awareness and behaviors in older drivers. We developed an intervention that provides feedback on accuracy of self-awareness of driving performance using a workbook, and examined its effectiveness using a prospective design with a follow-up after two months. Japanese drivers aged between 69 and 87 (Mean = 73.96) years were assigned to either the intervention group (n = 26) or the wait-list control group (n = 27). All participants were asked to assess their own driving performance by completing a questionnaire. They also completed an on-road driving assessment that involved driving on a public road while wearing an electronic device that measured their actual driving behaviors, accompanied by a driving instructor who sat in the passenger seat and assessed the participant's driving performance (expert assessment). Thereafter, only the intervention group received the immediate intervention (first wave). One month later, the intervention group completed the booster intervention by post. Two months after the first wave, both groups completed the questionnaire and on-road driving assessment again (second wave). Result revealed that discrepancy between self-assessment and expert assessment reduced in only the intervention group between the two waves. This finding suggests that the intervention was able to improve the accuracy of self-assessment. Furthermore, the expert assessment improved in the intervention group between the two waves, but this change was not observed in the control group. Similar trend was evident for vehicle speed at intersections with a stop sign but the result was not statistically significant. Changes in head rotation at intersections requiring turn in the intervention group did not differ from those in the control group. Improved accuracy of self-assessment as a result of the intervention could have led to improved general driving performance, but did not influence head rotation.